FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA TEKNISI GIGI DI KOMUNITAS OP PTGI - Yeyen Gumayesty; Yuyun Priwahyuni; Dwi Sapta Aryantiningsih; Risa Amalia (Ensiklopedia of Journal, 2023)
Work fatigue is a pattern that arises in a situation that generally occurs in workers. The causes of work fatigue are related to the nature of work, work intensity, high mental and physical endurance, working environment conditions, nutritional status, and workload. In the process of making dentures, dental technicians are likely to experience fatigue because they have to meet targets or finish making dentures according to the time requested by the dentist. In addition, there are other factors that can interfere with concentration at work resulting in fatigue and work accidents, such as scratches on the hands by grinding machines, punctured orthodontic wires and other possibilities (Nisa & Martiana, 2013). Research Objectives To determine the factors associated with work fatigue in dental technicians in the Indonesian Dental Technician Association Professional Organization Community (OP PTGI) in 2022. This type of research is quantitative analytic with a cross sectional design. The research was conducted at the Dental Laboratory. The research sample is 94 respondents. Data collection was carried out by distributing questionnaires using the Google form. The results showed that the majority of respondents experienced work fatigue, 52 people (55.3%). Bivariate analysis of all independent variables showed a significant relationship, namely age P-value 0.036, nutritional status P-value 0.022, workload P-value 0.025 and years of service with P-value 0.080. It is hoped that the research location can adjust the physical abilities and work capacity of dental technicians in the division of tasks to avoid work fatigue.